The Basque Issue and the Spanish Rule of Law: Report on the UPV/EHU “Ultima Ratio” Seminar - Xabier Ezeizabarrena (Oñati Socio-Legal Series)
This paper resumes the seminar organised by the International Institute for the Sociology of Law, the University of the Basque Country and the Basque Studies Society too in San Sebastian Campus and Oñati during the 2nd and 3rd of February 2012, with the presence of certain relevant experts from academia and practitioners. The ultima ratio principle was analysed from different perspectives and, in particular, within the complex context of implementation of the Rule of Law within the Basque Country.